System for Relay Protection Command Transmission by High-Voltage Lines - D. A. Yenkov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Development of a system for relay protection command transmission by high-voltage lines is shown in the paper. The paper describes an architecture of the system, main principles of its operation, engineering aspects of the development that is accomplishment of technical requirements, solution of trades-off. Justification of the selected design and an algorithm of the reliable detection of relay protection signals are given in the paper.